Accommodations for Students With Disabilities and Associated Barriers in Nursing and Psychiatric Nursing Education: Mixed-Methods Research - Thomson, Andrea; Baxter, Catherine; Dyck, Sherri; Magnusson, Michelle; Cleland, Michelle (Quality Advancement in Nursing Education / Avancées en formation infirmière)

(untitled) (Canadian Association of Schools of Nursing / Association canadienne des écoles de sciences infirmières, 2025)
Background: The experience of disability is often overlooked within equity, diversity, and inclusion initiatives in nursing education. Nursing students who self-identify as having a disability or disabilities have reported issues regarding accessibility and accommodations. Nurse educators have reported general uncertainty regarding ways to support students, especially within clinical practice settings.Purpose: The purpose of the study was to investigate the perceptions of nursing and psychiatric nursing students and faculty, with a focus on accommodations and associated barriers.Methods: Mixed-methods research was conducted to answer the following question: What accommodation practices promote or limit the inclusion of nursing and psychiatric nursing students with disabilities in theory and clinical practice settings? Data were collected through an anonymous online survey. A total of 95 responses were included in the analysis. Participants included students in undergraduate degree programs in nursing (n = 21) and psychiatric nursing (n = 22), academic nursing/psychiatric nursing faculty (n = 49), and accessibility professionals (n = 3) in Western Canada.Results: Two main themes were derived from the parallel analysis of the qualitative and quantitative data. The first theme focused on the provision of reasonable accommodations and the second focused on attitudes towards nursing and psychiatric nursing students with disabilities. Students who received accommodations reported that accommodations contributed to their success in the classroom environment (94%), skills lab (86%), and clinical setting (86%). The attitudes of participants towards accommodations were largely favourable. However, barriers to accessing accommodations were noted, mainly within clinical settings. The faculty participants identified lack of knowledge on accommodation processes and a lack of time to implement individual accommodations as a barrier. While the majority (74%) of participants agreed that students with disabilities could meet the theory requirements of professional programs, only half of the participants thought that these students could meet the clinical program requirements. Significant differences in responses were evident between participants who self-identified as having a disability or disabilities and those who did not.Conclusion: The findings highlight the need for effective accommodation processes for nursing students with disabilities, particularly within clinical environments. There is also a need for increased education, support, and resources for faculty to improve their levels of preparedness.